Current state and trends of development of agricultural enterprises specializing in livestock in Ukraine - POLENKOVA, Maryna (Economics. Finances. Law, 2020)
The paper describes the current state of the livestock industry and the problems that accompany it. The volumes of cultivation and sale for slaughter of farm animals, as well as the volumes of production of milk, eggs, wool, honey are analyzed. Significant structural changes during 2000-2019 in meat production by agricultural enterprises were revealed. The clustering of regions of Ukraine under similar conditions of development of the enterprises of the agricultural sector specializing in animal husbandry is carried out. According to the results of the analysis, 4 clusters were identified, which gave rise to the possibility of forming (developing) joint effective organizational and economic mechanisms to intensify the development of livestock enterprises, favorable for implementation within the cluster. Sustainable development of agriculture, including livestock, is essential to reduce poverty and ensure food security and nutrition, designed to meet the growing demand of the world's growing population for safe and guaranteed affordable food of animal origin, which is grown in compliance with increasingly stringent requirements, while protecting the environment. In the process of this study, attention is focused on the development trends of enterprises specializing in animal husbandry. The current state of the livestock industry is characterized by a number of problems, manifested in the following: – imbalance in the development of the agricultural sector: livestock significantly lags behind in terms of development compared to the crop sector; – low level of commodity production: the share of households in the production of livestock products, especially in the livestock sector, remains decisive; – low investment attractiveness: high cost of money in combination with a long payback period constrains investment in the development of the industry; – Insufficient level of consumption: consumption of meat and dairy products per 1 person is lower than reasonable norms; – a threatening epizootic situation: the spread of African swine fever threatens the entire pig industry. The application of multifactor statistical (cluster) analysis made it possible to group the regions of Ukraine under similar conditions for the development of agricultural enterprises specializing in animal husbandry. This provides opportunities for the formation (development) of joint effective organizational and economic mechanisms to enhance the development of livestock enterprises, favorable for implementation within each cluster (subject to the specifics of each region).